Urgency of Regulating the Registration of Land Rights For Former Foreign/Chinese Assets - Lucy Erdika; Patricia Audrey Ruslijanto; Supriyadi (Faculty of Law, University of Jember, Indonesia, 2025)
The issue of legal certainty of land rights can be traced back to the history of the birth of the Indonesian nation, which is known to have had several periods of population settlement in its development. One of these issues is the Assets of Chinese Foreigners. It is known that the government has determined that Former Foreign/Chinese Assets has existed since 1957 and is a reaction to the emergency situation at that time. Normatively, the regulation of Former Foreign/Chinese Assets settlement refers to the Regulation of the Minister of Finance Number 62/PMK.06/2020 concerning the Settlement of Former Foreign/Chinese Assets. In this legal principle, there are four methods of settling Former Foreign/Chinese Assets, including being determined as assets of government agencies, being released with payment of compensation to the state, being returned to the legitimate party, and being declared completed under certain circumstances. In fact, the continuation of Former Foreign/Chinese Assets to this day is still a polemic in society. Moreover, it is known that in the settlement of Former Foreign/Chinese Assets assets there is a phenomenon of lawsuits between the state and its people. Of course, this is something strange, especially since the object of the lawsuit is a land title certificate which is in fact the result of a legal product from the state itself. So it requires further study regarding the obstacles and obstacles to completing Former Foreign/Chinese Assets.